The Impact of Regulatory Deregulation on the Effectiveness of Hazardous and Toxic Materials (B3) Management Permits at PT Futai Tanjung Merah - Rompas, Deizen D.; Muaja, Harly S.; Lembong, Roy Ronny (Jurnal Ilmu Hukum Kyadiren, 2026)
Amendments to environmental regulations under Law No. 11 of 2020 on Job Creation have generated significant implications for the environmental licensing framework, particularly in the management of Hazardous and Toxic Substances (B3). This study aims to provide a comprehensive examination of the technical procedures for implementing B3 management permits at PT Futai Tanjung Merah, Bitung City, in accordance with Law No. 32 of 2009, Government Regulation No. 74 of 2001, and Government Regulation No. 101 of 2014. It also analyzes the administrative, technical, and institutional barriers that affect the effectiveness of implementation. Employing a descriptive qualitative design with a juridical-empirical approach, this research utilizes interviews, field observations, and legal document analysis as its primary data collection methods. The findings reveal that, while the implementation of B3 permits generally complies with existing regulations, their overall effectiveness remains constrained by policy overlaps, inadequate supervision, and limited public participation. The study concludes that achieving efficient environmental permit governance requires stronger synergy between legal certainty, institutional capacity, and public transparency.